Radiotherapy in Malignant Melanoma of the Nasal Cavity: A Rare Case Re-Irradiation Using Volumetric-Modulated Arc Therapy (VMAT) and Brachytherapy - Maren Irgiwi Fadlilah; Nova Agusta Isdiarto; Arundito Widikusumo (International Medical Journal Corp. Ltd, 2026)
Background: Malignant mucosal melanoma of the nasal cavity is a rare tumor with agressive characteristic and poor prognosis. Modern radiotherapy modalities such as Intensity-Modulated Radiotherapy (IMRT), VMAT, and brachytherapy offer the potential of the improvement of local control in tumor that historically known as radioresistant. The aim of this case report is to discuss malignant melanoma of the nasal cavity and the impact of radiotherapy, with a focus on re-irradiation using VMAT and brachytherapy in this diasase. Case description and Discussion: A man, 61 years old was diagnosed with malignant melanoma of the nasal cavity based on imaging and histopathology result. The patient underwent four cycles of chemotherapy, followed by external beam radiotherapy using IMRT technique with total dose 70 Gy/35 fractions. Post-treatment evaluation revealed residual mass, leading to re-irradiation using VMAT at 50 Gy/25 fractions, followed by Ir-192 brachytherapy at 16 Gy/4 fractions using a nasopharyngeal applicator. The cumulative total BED administered exceeded >160 Gy. Side effects on organs at risk were minimal, and post-treatment nasal bleeding and nasal congestion symptoms did not recur. Conclusion: A Multimodal approach combining IMRT, re-irradiation of VMAT, and brachytherapy demonstrates promising clinical outcomes in cases of malignant melanoma of the nasal cavity. The administration of a high cumulative Biological Effective Dose (BED) enables optimal tumor control without increasing toxicity to surrounding organs. This strategy is worth considering in the management of inoperable or locally recurrent head and neck mucosal melanoma.